Brief report: The Social Responsiveness Scale for adults (SRS-A): Initial results in a German cohort - Bölte, Sven (Springer New York LLC, 2012)
The Social Responsiveness Scale (SRS) is a tool for quantitative autism assessment in children and adolescents. The SRS-A addresses social responsiveness in adulthood. Reliability and validity using the German adaptation of the SRS-A was examined in 20 adults with Autism Spectrum Disorder (ASD), 62 with other mental disorders (CLIN) and 163 typically developing (TD) participants. Cronbach's alpha ranged from.71 (TD) to.89 (ASD). A SRS-A total score of 67 had a sensitivity of.85, and a specificity of.83 for ASD versus CLIN/TD. Correlations with established autism scales (ADOS, AQ, SCQ) were moderate to high (r =.25-.83). Results provide adequate preliminary support for the application of the SRS-A.